1977
DOI: 10.1177/00220345770560061901
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Excess Glucocorticoid Hormone on the Rate of Dentin Deposition in Rats

Abstract: A study was undertaken to determine the effect on the rate of deposition of dentin when high levels of adrenal glucocorticoid hormone are administered to rats. The results indicate that in the hypercorticoid rat, despite an increased eruption rate and a reduced width of incisor wall, no alteration occurs in the rate of dentin formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The noted formation of new dendn was not affected by the surgical trauni.a of heart transplantadon, as these rats showed the same results as rats only receiving corticosteroids. The effects of the steroids given are in agreement with previous studies with regard to reducdon of body weight (3)(4)(5)(6)14) and functional survival time ofthe heart allograft (7).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The noted formation of new dendn was not affected by the surgical trauni.a of heart transplantadon, as these rats showed the same results as rats only receiving corticosteroids. The effects of the steroids given are in agreement with previous studies with regard to reducdon of body weight (3)(4)(5)(6)14) and functional survival time ofthe heart allograft (7).…”
Section: Discussionsupporting
confidence: 89%
“…Contradictory results are also found in studies of the effect of corticosteroids on rat incisors (2)(3)(4)(5). In the investigation by AN-NEROTH & BLOOM (2) excessive formation of bone-like substances and disorganized odontoblasts was found in the pulp chamber of the incisors after daily injections of corticosteroids in high doses (50 mg) for 8 days to adult rats.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, the results of animal experiments were not unanimous concerning GCs’ effect on dentin formation. Ball et al [ 31 – 33 ] observed in three trials that rats given subcutaneous injections of corticosteroids had narrower dentin walls, resulting in larger pulp chambers in the incisors. After administering corticosteroids to freshly weaned rats, Johannessen et al [ 34 ] discovered that dentin development in the molars was suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some authors represent the statement that during pre-functional eruptive phase and early functional eruptive phase of teeth can be recorded decrease of the rate of synthesis and release of dentin [15]. Other researchers accentuate on the role of corticosteroids for stimulation of apposition of abundant pre-dentin tissue, with parallel and subsequently organized and performed process of accomplishment of predentin mineralization [12,16].…”
Section: Advances In Dentistry and Oral Healthmentioning
confidence: 99%